Christ Siemens Touraine syndrome: Two case reports and felicitous approaches to prosthetic management - Navanith Renahan; Renju Raj; R Balagopal Varma; J Suresh Kumar (Wolters Kluwer Medknow Publications, 2015)
Ectodermal dysplasia is a heterogeneous group of inherited disorders, which exhibit a classic triad of hypohydrosis, hypotrichosis, and hypodontia. Hypohidrotic or anhidrotic ectodermal dysplasia or Christ Siemens Touraine syndrome is the most common condition among ectodermal dysplasia patients. This is a case report on two Christ Siemens Touraine syndrome cases and two different approaches to prosthetic management.